O internato de medicina de família e comunidade na UERJ: uma análise a partir das perspectivas do interno, do preceptor e do docente - Itaborahy, Lorena Mega (2025)
This dissertation investigates the teaching-learning process within the Family and Community Medicine (FCM) internship at the Universidade do Estado do Rio de Janeiro (UERJ), from the perspectives of interns, preceptors, and faculty members. The main objective is to understand how the necessary competencies are being developed during the internship and to identify the essential conditions for this development. An exploratory study was conducted using a qualitative approach, employing semi-structured interviews with graduates of the internship and focus groups with preceptors and faculty to collect data, allowing for a multidimensional analysis of the experiences and perceptions of those involved. The results revealed the inherent complexity of the MFC internship, highlighting its significant contributions to the training of generalist physicians. The internship offers a unique opportunity to broaden students' understanding of the health-disease process, developing crucial competencies for a more humanized, comprehensive medical practice aligned with the principles of the Unified Health System and Primary Health Care. Additionally, the internship challenges the traditional hospital-centered model, promoting a more holistic and integrated view of health care. The study identified important challenges, such as the need for better integration between teaching and service, effective communication between the university and preceptors, and clarity in the roles and responsibilities of each participant in the educational process. These challenges indicate the need for ongoing improvement strategies. The dissertation concludes that, despite the difficulties, the FCM internship at UERJ is a privileged space for medical training, aligned with national curricular guidelines. It recommends expanding the adoption of innovative pedagogical approaches that value students’ autonomy, protagonism, and critical-reflective training, preparing them for a medical practice committed to social health needs